Knowledge construction process in online learning - Rahman, Saemah; Mohamad Yassin, Ruhizan; Jusoff, Kamaruzaman; Mohd Yassin, Siti Fatimah; Mohd Nordin, Norazah; Mohd Yusof, Melor (IDOSI Publications, 2011)
One of applications in online learning environment is the use of forum or discussion through online communication facilities as a learning activity. This paper focuses on the process of knowledge construction in online discussion designed to be used with mobile technology. The research participants comprised 45 postgraduate students enrolled in a research methodology course. These participants were involved in the online discussion as one of the mode of delivery for the course. Data were collected through open ended questionnaire to tap into their perceptions about online learning activity through online discussion. They were also asked to do metacognitive reflections to explain step by step on how do they make conclusion on the meaning of a specific concept from the online discussion. Data were analysed using content analysis as the means of analysis. Result of the study shows majority of respondents agreed that online discussion helps the knowledge construction process through critical examinations of other peoples idea in the discussion. Overcoming psychological barriers is one of the important aspects offered by online environment that facilitate students involvement in constructing knowledge as compared to face to face discussion. Further analysis on the learning process revealed pattern of steps used by the students in constructing the meaning through the discussion process.